Impact of Economic Factors on Sustainability of the Fishing Industry of the Russian Arctic Zone - Sergey S. Vopilovskiy (Арктика и Север)
The analysis of the influence of actual external and internal economic factors on the work of the fishing industry in general and in the Arctic zone in particular shows the stability and ability of the Russian fishery complex to fulfil the tasks of implementing the Food Security Doctrine of the Russian Federation and other strategic regulatory documents. Timely work of the state legislative bodies in decision-making at all levels of management in the current situation is noted. Key economic factors (export and import, supply and demand, shipbuilding and ship repair, logistics, etc.) that have direct and indirect impact after the in-troduction of sanctions are considered. The paper analyses the key performance indicators of the Russian fishery complex, provides an analytical review of the demand for fresh-frozen fish in the North-West re-gion, the relationship between the population’s income and the consumption of fish and fish products in the country. The primary role of scientific support of the fishing industry in the successful realization of the general goals and achievement of the set tasks is emphasized. An assumption about opening of new logistic routes and expansion of geography of fish and fish products supplies to African and Latin American countries, countries of Asia-Pacific region is made on the basis of assessment of modern international relations. It is determined that the construction and repair of the fishing fleet in modern conditions is of concern to the state structures and fishing business community. The measures of state support of shipbuilding plants of the country are considered, the proposal on creation of ship repair cluster in the Arctic zone of the Russian Federation is substantiated.